Opportunities and challenges in Asian bee research and conservation - Warrit, Natapot; Sinu, Palatty Allesh; Mu, Junpeng; Belavadi, Vasuki; Brockmann, Axel; Buchori, Damayanti; Dorey, James B.; Hughes, Alice; Krishnan, Smitha; Ngo, Hien T.; Priawandiputra, Windra; Zhu, Chao-Dong; et al. (Elsevier, 2023)
The challenges of bee research in Asia are unique and severe, reflecting different cultures, landscapes, and faunas. Strategies and frameworks developed in North America or Europe may not prove applicable. Virtually none of these species have been assessed by the IUCN and there is a paucity of public data on even the basics of bee distribution. If we do not know the species present, their distribution and threats, we cannot protect them, but our knowledge base is vanishingly small in Asia compared to the rest of the world. To better understand and meet these challenges, this perspective conveys the ideas accumulated over hundreds of years of cumulative study of Asian bees by the authors, including academic, governmental, and other researchers from 13 Asian countries and beyond. We outline the special circumstances of Asian bee research and the current state of affairs, highlight the importance of highly social species as flagships for the lesser-known solitary bees, the dire need for further research for food security, and identify target research areas in need of further study. Finally, we outline a framework via which we will catalyze future research in the region, especially via governmental and other partnerships necessary to effectively conserve species.